2020
DOI: 10.4025/actascianimsci.v43i1.49844
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various heat-treatment methods on colostrum quality, health and performance of dairy calves

Abstract: To investigate the effect of feeding heat-treated colostrum at different duration on the health and performance, 48 Holstein calves were enrolled randomly into four treatment groups before first feeding and consumed untreated colostrum (H0, n = 12), heat-treated colostrum at 60ºC for 30 min. (H30, n = 12), heat-treated colostrum at 60ºC for 60 min. (H60, n = 12) and heat-treated colostrum at 60ºC for 90 min. (H90, n = 12). Blood samples were collected for analyses of IgG and protein profile at 0, 6, and 24h of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Similar to previous studies, Hesami et al (2020) studied the impact of different pasteurization temperatures and duration such as 60 °C for 30, 60, and 90 min respectively on IgG concentration of bovine colostrum. The feeding pasteurized bovine colostrum effect on the health and performance of Holstein calves were also evaluated in this study.…”
Section: Low-temperature Long-time (Ltlt) Pasteurizationmentioning
confidence: 84%
See 1 more Smart Citation
“…Similar to previous studies, Hesami et al (2020) studied the impact of different pasteurization temperatures and duration such as 60 °C for 30, 60, and 90 min respectively on IgG concentration of bovine colostrum. The feeding pasteurized bovine colostrum effect on the health and performance of Holstein calves were also evaluated in this study.…”
Section: Low-temperature Long-time (Ltlt) Pasteurizationmentioning
confidence: 84%
“…In conclusion, calves fed pasteurized colostrum had a better overall health status, whereas calves fed with unpasteurized colostrum had a lower prevalence of diarrhea-induced pathogens. During lactation, calves’ health, growth characteristics, and physical performance were improved by feeding pasteurized colostrum ( Hesami et al, 2020 ).…”
Section: Thermal Treatment Methodsmentioning
confidence: 99%
“…Rafiei et al and Hesami et al showed that ADG and weaning weight were greater in calves fed heated colostrum. 65,68 Monitoring daily weight gain allows the assessment of efficiency and consistency of growth over a suckling period. Our study identified mean daily weight gains in calves fed heated or unheated colostrum of 0.54 and 0.49 kg/day, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in serum GH concentration in calves fed colostrum may result at least partly from the effects of absorbed colostral GH releasing factor (GHRF) that stimulates the release of endogenous GH by the pituitary gland of neonatal calves. Rafiei et al and Hesami et al showed that ADG and weaning weight were greater in calves fed heated colostrum 65,68 . Monitoring daily weight gain allows the assessment of efficiency and consistency of growth over a suckling period.…”
Section: Discussionmentioning
confidence: 99%